Language shift towards English among Malayalam speakers in Malaysia / Wanitha a/p K. A. Govindan - K.A. Govindan, Wanitha (2014)
The purpose of this research is to study the shift from Malayalam to English among the Malayalees in Malaysia and to assess the linguistic vitality of the Malayalam language in Malaysia. The first phase of the study focused on the language choice and language shift of the Malayalee speakers. The data gathering in the first phase used a series of interviews, questionnaire and cross-sectional survey. The second phase of the research which involved assessing the linguistic vitality of Malayalam language in Malaysia was carried out using a language vitality test, and benchmarking some of the factors that indicate the vitality of Malayalam based on “Language Vitality and Endangerment” by the UNESCO Ad Hoc Expert Group on Endangered Languages (2003). The results of the study showed that there is an increasing shift from Malayalam towards English among Malayalees in Malaysia due to several factors. This include the fact that Malayalam is not offered in schools as an elective language, it is not well represented by the media, it is not used outside the domains of family and society, and the general perception is that it is more important to learn English than Malayalam. The linguistic vitality of Malayalam too was found to be in the unsafe category which means that little effort is being made to maintain the Malayalam language and it shows that there is a gradual decline in its use among Malayalees in Malaysia.